PENGAJARAN BAHASA INGGRIS DALAM KURIKULUM 2013: SUATU TINJAUAN DAN PERSPEKTIF - Setiawan, Iwan (Jurnal Ilmiah Pendidikan dan Keislaman, 2021)
This study aimed at reviewing ELT and in use Curriculum 2013 and revealing teachers’ perspectives regarding its implementation. This was qualitative research using open-ended interview. Its participants were 5 teachers from 5 different schools, ranging from pilot to accompanying schools. The result shows that there are some differences between K-13 and KTSP in terms of curricular terminologies, the emphasis of students’ affective aspect, and learning approach; it is still difficult to create lesson plans of K-13 syllabi; overloaded aspects in students’ report cards to be assessed; confusing instructional models; lack of socialization and involvement of the teachers; K-13 uses a holistic approach; extra hours for character and religious education; autonomous learning; compact materials; reduction of English teaching hours; removal of English from elementary school; insufficient materials at primary levels; and so forth. Hence, this study concluded though Curriculum 2013 has already been well organized, yet it still needs more planning, socialization, involvement of many parties, and improvement of some factors should be more take into account by all elements of national education for the improvement of its implementation